2022
DOI: 10.1038/s41598-022-06519-7
|View full text |Cite
|
Sign up to set email alerts
|

fMRI-based validation of continuous-wave fNIRS of supplementary motor area activation during motor execution and motor imagery

Abstract: Compared to functional magnetic resonance imaging (fMRI), functional near infrared spectroscopy (fNIRS) has several advantages that make it particularly interesting for neurofeedback (NFB). A pre-requisite for NFB applications is that with fNIRS, signals from the brain region of interest can be measured. This study focused on the supplementary motor area (SMA). Healthy older participants (N = 16) completed separate continuous-wave (CW-) fNIRS and (f)MRI sessions. Data were collected for executed and imagined h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(66 citation statements)
references
References 62 publications
2
37
0
Order By: Relevance
“…In addition, both semi-simulated and real data the quality measures changed for Δ[ HbR ] after correction, which confirms that Δ[ HbR ] is influenced by SA too and should thereby be corrected accordingly. 26…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, both semi-simulated and real data the quality measures changed for Δ[ HbR ] after correction, which confirms that Δ[ HbR ] is influenced by SA too and should thereby be corrected accordingly. 26…”
Section: Discussionmentioning
confidence: 99%
“…The real data set comprised ME and MI data. Details of the study design can be found in Klein et al 26 In short, N = 32 healthy elderly individuals performed five motor tasks, that is, a self-paced sequential finger tapping task that was physically performed with either the left (ME LEFT) or the right (ME RIGHT) hand or kinesthetically imagined with either the left or the right hand. The fifth task was the kinesthetic imagination of an arbitrarily chosen whole-body movement involving both arms and legs.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations